Education Budget Savings from Ending Child Marriage and Early Childbirths : The Case of Niger - Wodon, Quentin (Taylor and Francis, 2018)
Ending child marriage and early childbirths would reduce total fertility rates and population growth especially in countries with a high incidence of child marriage, early childbirths, or both. Savings for public budgets could be large. This article relies on demographic projections and a UNESCO costing model for the provision of education by governments to estimate savings that could result from ending child marriage and early childbirths for public education budgets. The analysis is conducted for Niger, the country with the highest rate of child marriage in the world.